Pengaruh Pembelajaran dengan Pendekatan Saintifik terhadap Motivasi dan Prestasi Belajar Mata Pelajaran Pendidikan Agama Islam pada Kelas VII SMP Negeri 1 Wringinanom Gresik - Vialinda Siswati (PROGRESSA: Journal of Islamic Religious Instruction, 2017)
A glimpse of what is being taught Islam shows how much this religion intersect with science and education, for example, paragraphs 4 and 5 of Surah Al-Alaq, God Almighty, as a primary teacher, taught man what he did not know by means of a pen, « (5) يعلم لم ما الانسان علم) 4) ابلقلم علم الذی ,(when the Koran highlighted the importance of the pen as a tool for learning and spreading knowledge to swear to the pen, «يسطرون وما والقلم ن «ie "Noon. I swear by the pen and what the angels write. ", then all substance is solving educational problems existing in Islamic Education. Solve the problem of how to use the various disciplines in the face of an integrative way of life seemed quite handed over to the students to develop competencies naturally. The purpose of this study were: 1) Describe the effect of learning with a scientific approach to achievement motivation in class VII SMP Negeri 1 Gresik Wringinanom. 2) Describe the effect of learning with a scientific approach to learning achievement in Grade VII SMP Negeri 1 Gresik Wringinanom. From the analysis can be summarized as follows: 1) From the analysis it is known that the scientific approach to learning with an effect on achievement motivation in class VII SMP Negeri 1 Gresik Wringinanom value obtained Fhitung 15 641 (significance F = 0.000). So Fhitung> Ftabel (15 641> 1.60) or Sig F <5% (0.000 <0.05). This means that learning with the scientific approach effect on achievement motivation in class VII SMP Negeri 1 Gresik Wringinanom. then the null hypothesis (H0) is rejected and Working Hypothesis (H1) is accepted. 2) From the analysis show that the scientific approach to learning with an effect on learning achievement in grade VII SMP Negeri 1 Gresik Wringinanom value obtained Fhitung 2,924 (significance F = 0.009). So F count> F table (2,924> 1,60) or Sig F <5% (0.009 <0.05). This means that learning with the scientific approach to influence the learning achievement in grade VII SMP Negeri 1 Gresik Wringinanom.